On the development of the investigation principle in didactics - Bernotas , V. (Psichologija, 1969)
The investigation principle plays an important part in harmonious development of personality, in preparing it for life and practical activities. It enables pupils to master knowledge more deeply and consciously, develops creative thought and independence. In this article the main attention is devoted to the problem of the inception of the investigation principle and its development throughout the history of pedagogics. A brief characteristic of this principle, its essence and tasks are also given. Much consideration is given to the analysis of the Dalton plan and projects’ method, and the reasons for adopting these systems of training first in the U.S.A. and later in schools of the Soviet Union. Different variants of the investigation principle are described. A review of the latest Soviet and foreign pedagogical literature on the subject is given, and ways of further development of this problem are shown.
Keywords: didactics; investigation principle